Front Cover, Volume 23 Issue 6. Issue 6 (16th May 2017) - Stabach, Jared A.; Rabeil, Thomas; Turmine, Vincent; Wacher, Tim; Mueller, Thomas; Leimgruber, Peter
Abstract : The cover image, by Jared A. Stabach et al., is based on the Biodiversity Research On the brink of extinction—Habitat selection of addax and dorcas gazelle across the Tin Toumma desert, Niger, DOI:10.1111/ddi.12563 . Photo Credit: Thomas Rabeil, Sahara Conservation Fund.